Accumulation of Hydroxyl Fatty Acid in Lactobacillus sakei Y-20 Cells Cultivated under Stress Conditions and Expression of Fatty Acid Hydroxylase. (2nd January 2018) - Kanauchi, Makoto; Nagata, Ayaka; Kondo, Ayaka
ABSTRACT: Fruit aroma lactones such as γ-dodecalactone contained in whisky are produced by yeast from precursor hydroxyl fatty acids created by lactic acid bacteria from fatty acids. Application of the aroma lactone in brewery or whisky/spirits production requires knowledge of the conditions of hydroxylation by enzyme activity and its expression in bacteria. Hydroxyl fatty acid was produced more efficiently at 15°C than at 30°C. The 10-hydroxyl stearic acid (10-HSA), which accounts for more than approximately 60% of fatty acids in cell membranes, is converted from oleic acid (OA). However, the hydroxylase (FAHase) did not convert other fatty acids to hydroxyl fatty acid. The fatty acid hydroxylase in the strain was able to react only with OA. Although the strain was able to grow in the medium containing OA under low pH, alcohol, and metal ion stress conditions, 10-HSA accumulated only to a slight degree. The expression of FAHase in the medium containing OA at 15°C was 2.38 times that of the medium without OA. The expression of FAHase in the pH 2.0 condition was 1.7 times that of the control. Furthermore, in a medium containing iron ions, the expression of FAHase was more than twice that of the control.